ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN TUNA AND SHRIMP EXPORTS IN THE UNITED STATES MARKET - Nurkhasanah, Anissa Aprilia; Putera, I Gede Suweda Anggana; Maulidiyah, Vika; Mazaya, Amalia Febryane Adhani (Jurnal Perikanan Unram, 2025)
Indonesia is exporting less prawns and tuna to the United States in 2021–2023. An analytical investigation on the competitiveness of Indonesian prawn and tuna products supplied to destination nations like the USA is required in light of these facts. The objective of this study is to examine the growth of Indonesian prawn and tuna exports to the US as well as their competitiveness in this market. This study examines Indonesian prawn and tuna commodities' export competitiveness in the US market from 2012 to 2022. Pustaka, UN Comtrade, Trademap, the Central Statistics Agency (BPS), and the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia (KKP RI) are the sources of the data. The Constant Market Share (CMS) and Revealed Comparative Advantage (RCA) approaches are the analytical techniques employed in this study. The results show that the trend of leading export commodities, one of which is still dominated by shrimp. Shrimp is the main commodity with export volume increasing significantly from 197.4 million (kg) in 2018 to 250.7 million (kg) in 2021 but experiencing a decline in 2022. The trade value of American shrimp, shrimp consists of large shrimp cold air (0306.16) and tiger prawns (0306.17). The trade value of American tuna, tuna consists of fresh tuna, frozen tuna and tuna fillet. Fresh tuna consists of yellowfin tuna (0302.32) and 0302.34 bigeye tuna. Frozen tuna consists of longfin tuna/albacore (0303.41), yellowfin tuna (0303.42), skipjack tuna (0303.43) and southern bluefin tuna (0303.46); Tuna fillet consists of skipjack tuna (0304.87). The competitiveness of tuna and shrimp in the United States has strong competitiveness.